2006
DOI: 10.1103/physrevc.74.069902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: α-nucleus potentials, α-decay half-lives, and shell closures for superheavy nuclei [Phys. Rev. C73, 031301(R) (2006)]

Abstract: Systematic α-nucleus folding potentials are used to analyze α-decay half-lives of superheavy nuclei. Preformation factors of about several per cent are found for all nuclei under study. The systematic behavior of the preformation factors and the volume integrals of the potentials allows to predict α-decay energies and half-lives for unknown nuclei. Shell closures can be determined from measured α-decay energies using the discontinuity of the volume integral at shell closures. For the first time a double shell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 38 publications
2
82
0
Order By: Relevance
“…They are also similar to those obtained by using the semi-microscopic potential III of Ref. [11] at the same energies, or derived from the analysis of α-decay [2,74].…”
Section: (αα) Semi-microscopic and Phenomenological Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…They are also similar to those obtained by using the semi-microscopic potential III of Ref. [11] at the same energies, or derived from the analysis of α-decay [2,74].…”
Section: (αα) Semi-microscopic and Phenomenological Analysissupporting
confidence: 84%
“…it is used to unify the bound and scattering α-particle states [1], to analyze the superheavy nuclei α-decay halflives [2], in basic nuclear astrophysics applications [3] and for the estimation of radiation-damage effects in fusion test facilities and accelerator-driven systems. A successful global optical potential was formerly obtained by Nolte et al [4] only for α-particle energies above 80 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…Many nuclei under study are unstable, and electron scattering data are not available in [41]. Therefore, the densities for all N = 50 nuclei in the present study were derived in the same way as in [25,36]; there it was shown that an averaged twoparameter Fermi distribution provides reasonable densities over a broad mass range by a simple scaling of the radius parameter r ∼ A 1/3 . As will be discussed later, the resuls do not show a strong dependence on the radius parameter.…”
Section: A Folding Potentialsmentioning
confidence: 95%
“…Further information on the systematics of folding potentials has been obtained from the analysis of α-decay data for superheavy nuclei (e.g. [25,26,27,28,29,30,31]), for neutron-deficient p-nuclei [32,33,34], and for nuclei slightly above the doubly-magic N = Z = 50 nucleus 100 Sn [35,36]. The present work extends the study of [36] to lighter N = 50 nuclei because the double-folding potentials have proven to be reliable in such a broad range of masses.…”
Section: A Folding Potentialsmentioning
confidence: 99%
“…The process of decay of alpha (α) particle from heavy and super-heavy nuclei has been studied intensively in the past few years [1][2][3][4][5][6][7][8][9][10][11][12]. In many papers a simple two-body model was applied [11][12][13] and in most papers a potential was derived that was able to fit the measured α-decay half-lives of the alpha emitters.…”
Section: Introductionmentioning
confidence: 99%